2017
DOI: 10.1590/1807-1929/agriambi.v21n12p834-839
|View full text |Cite
|
Sign up to set email alerts
|

Physiological characteristics and yield of ‘Pérola’ pineapple in the semi-arid region

Abstract: The objective of this study was to evaluate the physiological characteristics and yield of ‘Pérola’ pineapple subjected to irrigation with saline water in the semi-arid region of Bahia. The experiment was conducted in randomized blocks with five treatments, represented by irrigation depths: 100% ETc, using water with electrical conductivity (ECw) of 0.75 dS m-1, and 50, 75, 100 and 125% ETc, using water with ECw of 3.6 dS m-1. The experiment used a drip irrigation system and pressure-compensating emitters with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 18 publications
0
6
0
6
Order By: Relevance
“…Em condições de salinidade com água de 3,6 ds m -1 não se verificou as altas correlações do IAF no 13° mês, assim como verificado em condições com água de 0,75 ds m -1 . Possivelmente os efeitos da salinidade, tais como, alterações nos processos de absorção, transporte, assimilação e distribuição de nutrientes na planta (SANTOS; BRITO, 2016) reduziram as características morfológicas das plantas com diminuição da produtividade do abacaxizeiro em condições semiáridas (BRITO et al, 2017) e, desta forma, as correlações foram baiixas.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Em condições de salinidade com água de 3,6 ds m -1 não se verificou as altas correlações do IAF no 13° mês, assim como verificado em condições com água de 0,75 ds m -1 . Possivelmente os efeitos da salinidade, tais como, alterações nos processos de absorção, transporte, assimilação e distribuição de nutrientes na planta (SANTOS; BRITO, 2016) reduziram as características morfológicas das plantas com diminuição da produtividade do abacaxizeiro em condições semiáridas (BRITO et al, 2017) e, desta forma, as correlações foram baiixas.…”
Section: Discussionunclassified
“…Em condições de irrigação com água salina de condutividade elétrica de 3,6 dS m -1 verificou-se que ocorre redução da produtividade do abacaxi quando se compara com água de 0,75 dSm -1 (BRITO et al, 2017). Assim, mensurações morfofisiológicas e suas correlações com as características produtivas da cultura podem ajudar no entendimento e otimização da aplicação com água salina em condições semiáridas.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…However, since the pineapple has characteristics of a CAM plant, as shown in this study by the values of Yield, RFd and qp, it is suggested that applying saline water does not have a negative impact on fluorescence characteristics evaluated over the study. Decreases in yield observed when applying saline irrigation water under semiarid conditions (Brito et al, 2017) might be due to other salinity-related effects such as changes in nutrient uptake, transport, assimilation and distribution throughout the plant (Santos and Brito, 2016).…”
Section: Depthsmentioning
confidence: 99%
“…The irrigation intervals used for growing edible pineapple in the open are flexible, and typically range from two to seven days (AZEVEDO et al, 2007;SOUZA et al, 2012b;SANTANA et al, 2013). This flexibility is mainly due to the acid metabolism of crassulaceae (CAM), which affords the crop a high level of water use efficiency and resistance to water deficit (BRITO et al, 2017;CARR, 2012). As they belong to the same species, the ornamental variety could supposedly be irrigated at greater intervals, similar to those of the edible variety.…”
Section: Introductionmentioning
confidence: 99%